PELAKSANAAN PROGRAM REHABILITASI SOSIAL RUMAH TIDAK LAYAK HUNI (RS-RTLH) OLEH DINAS SOSIAL DI KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU (STUDY KASUS DI KECAMATAN MORO) - Zalmi Hidayat; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The implementation is one of the series in activities are planned and carried out by the gradual implementer who have oained authority or order from executive in the form of laws that influence the implementation activities. Related of the social services program karimun district has an agency authorized to implement of home uninhabitable social rehabilition program.The aims is to help the problem of people wo have a medium economy in terms protection of residence. Residence is one of the basic needs that must be owned by everyone. This research aims to identity and analysis the implementation of home uninhabitable social rehabilitation program at the moro district.this is a descriptive qualitative study which gives a clear and detailed illustration based on the facts was found in the observation.The theory that used as an analysis in this study is George C. Edward theory in widodo 2011 interprets the factors that affect one is success or failure in the implementation of home uninhabitable sosial rehabilitation program in the collection data use observation and interview technique kualitative technique.After research had been done we found that the implementation of home uninhabitable program which run by social department well and has eased the burden at moro district every year. Also there are problems are face in running the implementation of home uninhabitable social rehabilitation program that are human resourches lack of public awareness and undiscipline of time in practice it.Keywords: the implementation, home uninhabitable social rehabilitation program